Circulating tumor DNA analysis enables molecular characterization of pediatric renal tumors at diagnosis. Issue 1 (26th October 2018) - Jiménez, Irene; Chicard, Mathieu; Colmet‐Daage, Léo; Clément, Nathalie; Danzon, Adrien; Lapouble, Eve; Pierron, Gaelle; Bohec, Mylène; Baulande, Sylvain; Berrebi, Dominique; Fréneaux, Paul; Coulomb, Aurore; et al.
Abstract : Circulating tumor DNA (ctDNA) is a powerful tool for the molecular characterization of cancer. The most frequent pediatric kidney tumors (KT) are Wilms' tumors (WT), but other diagnoses may occur. According to the SIOP strategy, in most countries pediatric KT have a presumptive diagnosis of WT if they are clinically and radiologically compatible. The histologic confirmation is established after post‐chemotherapy nephrectomy. Thus, there is a risk for a small fraction of patients to receive neoadjuvant chemotherapy that is not adapted to the disease. The aim of this work is to perform molecular diagnosis of pediatric KT by tumor genetic characterization based on the analysis of ctDNA. We analyzed ctDNA extracted from plasma samples of 18 pediatric patients with KT by whole‐exome sequencing and compared the results to their matched tumor and germline DNA. Copy number alterations (CNAs) and single nucleotide variations (SNVs) were analyzed. We were able to detect tumor cell specific genetic alterations—CNAs, SNVs or both—in ctDNA in all patients except in one (for whom the plasma sample was obtained long after nephrectomy). These results open the door to new applications for the study of ctDNA with regards to the molecular diagnosis of KT, with a possibility of its usefulness for adapting the treatment early after diagnosis, but also for disease monitoring and follow up. Abstract : What's new? The analysis of cell‐free DNA (cfDNA) in pediatric patients with kidney tumors is of interest for the molecular diagnosis and early identification of aggressive disease subtypes. In this study, significant amounts of circulating tumor DNA (ctDNA) were successfully isolated from pediatric patients with malignant kidney tumors. Accurate copy number profile and mutation calling to identify specific tumor cell genetic alterations was performed with whole‐exome sequencing using only low volumes of blood (≥100 μL) and low amounts of cfDNA (≥4 ng). The findings suggest that ctDNA analysis can facilitate the molecular diagnosis of specific subtypes of pediatric kidney tumors, potentially enabling earlier treatment.